Approximation schemes for differential functional equations and algorithms their applications - Cherevko, Ihor; Tuzyk, Iryna; Ilika, Svitlana; Pertsov, Andrii (Vasyl Stefanyk Precarpathian National University, 2022)
Using the approximate finding algorithms for non-asymptotic roots of quasi-polynomials, a way for construct ing the coefficient areas of stability for linear differential equations with delay and finding the set of delay values for which the equation is asymptotically stable is suggested.